Anticholesterol Antibody: the way for Reduction of Hypercholesterolemia - Sarkar, D; Latif, SA; Aich, J; Uddin, SN (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):217-20. The abstract of this article is available on the PubMed website